2017
DOI: 10.1080/08941939.2017.1319995
|View full text |Cite
|
Sign up to set email alerts
|

Copious Irrigation Versus Suction Alone During Laparoscopic Appendectomy for Complicated Appendicitis in Adults

Abstract: The study findings revealed that copious irrigation of peritoneal cavity during laparoscopic appendectomy could decrease the incidence of postoperative intra-abdominal abscess in adult patients with complicated appendicitis. These patients also had faster postoperative recovery and lower hospital charges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 19 publications
0
34
1
1
Order By: Relevance
“…Previous studies have suggested that peritoneal irrigation during LA for complicated appendicitis could reduce the incidence of IAA [9,10]. This idea came from the phrase "dilution is the solution to pollution. "…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that peritoneal irrigation during LA for complicated appendicitis could reduce the incidence of IAA [9,10]. This idea came from the phrase "dilution is the solution to pollution. "…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of irrigation during LA to reduce the risk of IAA remains debatable. A few studies have evaluated the effectiveness of irrigation during LA; however, most focused on complicated appendicitis [9,12]. In addition, there is no evidence for irrigation during LA in uncomplicated appendicitis cases.…”
Section: Introductionmentioning
confidence: 99%
“…The study interval ranged from 1965 to 2016, and thus encompasses the prelaparoscopic era to the present day, including studies from healthcare centres across four continents. Three of the included studies were RCTs; the remainder were retrospective cohort studies. Four studies included analysis only of the paediatric population, two of which were performed entirely using open surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Several RCTs have compared appendicectomy performed with suction alone with various methods of lavage; however, no systematic analysis of such studies has been performed. The aim of this systematic review was to determine the benefit of lavage for appendicitis versus suction alone, focusing particularly on postoperative IAA and WI.…”
Section: Introductionmentioning
confidence: 99%
“…The RCT by Sun et al [6] concludes that irrigation during LA for complicated appendectomy, using at least 2-L normal saline in all four quadrants until no grossly purulent remnants are visible, implying that all the injected fluid is aspirated, reduces IAA incidence, shortens time to first anal exufflation and post-operative stay, and reduces hospital charge. This 348 A. Pasculli et al study has the potential of giving a LoE IB and GoR A, enhancing the process to further meta-analysis, and hopefully new guidelines.…”
Section: Introductionmentioning
confidence: 99%